The phenomenon of spiritual in dimensions of irrational: the context of intuition and faith - Ivanova, Nataliya (Psyhology & society, 2019)
It has been implemented the analysis of the problem of spirit in the parameters of classical philosophy and socio-cultural cognition. The research specifies features of “objective,” “subjective”, “theoretical” spirit and their relationship with the practice of socio-cultural life and humanitarian cognition. On this basis author singles the intentions of “spiritual”, including “intellectual intuition” as the basis for forming of capacity of creative and productive thinking. Based on the understanding of Hegel’s spirit in its various manifestations, the study shows that his influence is a reason of the change in the direction from natural to socialized human essence. The result is the formation of spiritual sphere, which is independent from materialistic existence and from single consciousness. This sphere in its manifestations – the objective, subjective, universal spirit – inner, spiritual dimension of created by people world, culture and society, the center of which is a thinking individual. One of the main characteristics of the spirit is practice as self-creative activity that gives it an ability to act as a universal force. On the bases of spirit in its integrity appears and actualizes cognitive activity and human thinking. Human as spiritual (thinking) substance belongs to the higher reality, which takes it beyond immediate practice. Therefore, the main characteristic of human as a spiritual creature is the desire to contribute to a higher being that peeks from the depths of social and cultural cognition. The study shows that the concept of  spirit correlates with intellectual intuition, which is the part of spirit energy and of thinking activity. The sphere of spiritual life realizes itself in the fullest way in philosophy and religion, because it contains irrational moments (intuition, faith). Religious verities always appear in the form of ideals of creative life-asserting, perfect in-verity being, which define the standard of harmonic and spiritual individual existence for future generations. All other religious verities and symbols are derived from them. The results of the study give the reason to emphasize that the true spiritual revelation about higher meanings and, respectively, “knowing faith”, can be achieved only through sincere cultural creativity, namely through such a cognitive ability as “intelligence of heart”.